2021
DOI: 10.1016/j.neuron.2020.09.042
|View full text |Cite
|
Sign up to set email alerts
|

High-Contrast In Vivo Imaging of Tau Pathologies in Alzheimer’s and Non-Alzheimer’s Disease Tauopathies

Abstract: All rights reserved. No reuse allowed without permission.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
227
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 192 publications
(238 citation statements)
references
References 95 publications
8
227
3
Order By: Relevance
“…Absolute MM/GBSA energies of PM-PBB3 are similar for both Tau AD and Tau PiD (−34.2 kcal·mol −1 for Tau AD and −34.3 kcal·mol −1 for Tau PiD ) ( Figure 5 A,B), confirming that PM-PBB3 binds to both kinds of tau filaments. This is in the agreement with recent experimental study that indicates binding of PM-PBB3 to Tau PiD and Tau AD is nearly similar [ 16 ]. On the other hand, the relative binding order of PM-PBB3 illustrates unique features of the Tau PiD protofibril when compared to that of Tau AD .…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Absolute MM/GBSA energies of PM-PBB3 are similar for both Tau AD and Tau PiD (−34.2 kcal·mol −1 for Tau AD and −34.3 kcal·mol −1 for Tau PiD ) ( Figure 5 A,B), confirming that PM-PBB3 binds to both kinds of tau filaments. This is in the agreement with recent experimental study that indicates binding of PM-PBB3 to Tau PiD and Tau AD is nearly similar [ 16 ]. On the other hand, the relative binding order of PM-PBB3 illustrates unique features of the Tau PiD protofibril when compared to that of Tau AD .…”
Section: Resultssupporting
confidence: 93%
“…In addition, this approach can be applied to the interaction of PET tracers with non-tauopathy off-targets, such as MAO-A/-B and other dementia/neurodegenerative proteins (amyloid-β or α-synuclein). Since previous studies confirmed relatively low affinities of tau tracers, [ 11 C]PBB3 and [ 18 F]PM-PBB3, for MAO-A/B and α-synuclein by in vitro radioligand binding assay [ 16 , 35 , 36 ], it will be interesting to perform side-by-side validation with both an in vitro assay and an MM/GBSA approach.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations